The application of distributed discrete event simulation algorithms to Concatenated LOcal-area and Wide-area Network (CLOWN) simulator - Carreon, Mario (2006)
The Concatenated LOcal-area and Wide-area Network (CLOWN) simulator is a network simulator programmed using object-oriented C that runs on a single processor. This study aims to take advantage of the inherent parallelism of network models by implementing a distributed Java version of CLOWN (D-CLOWN) that can operate in two modes: one using the conservative Null Message protocol, the other using the optimistic Time Warp protocol. This paper pinpoints issues arising from this new implementation, describes the high-level system architecture for model programmers, and provides benchmarks of the new system (and its different modes) as compared to a non-distributed Java version of CLOWN.
Thesis (M.S. Computer Science)--University of the Philippines Diliman.
Keywords: CLOWN (Network simulator).; Algorithms